If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(3x + -6) + 9x = 9 + 4(3x + -3) Reorder the terms: -2(-6 + 3x) + 9x = 9 + 4(3x + -3) (-6 * -2 + 3x * -2) + 9x = 9 + 4(3x + -3) (12 + -6x) + 9x = 9 + 4(3x + -3) Combine like terms: -6x + 9x = 3x 12 + 3x = 9 + 4(3x + -3) Reorder the terms: 12 + 3x = 9 + 4(-3 + 3x) 12 + 3x = 9 + (-3 * 4 + 3x * 4) 12 + 3x = 9 + (-12 + 12x) Combine like terms: 9 + -12 = -3 12 + 3x = -3 + 12x Solving 12 + 3x = -3 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 12 + 3x + -12x = -3 + 12x + -12x Combine like terms: 3x + -12x = -9x 12 + -9x = -3 + 12x + -12x Combine like terms: 12x + -12x = 0 12 + -9x = -3 + 0 12 + -9x = -3 Add '-12' to each side of the equation. 12 + -12 + -9x = -3 + -12 Combine like terms: 12 + -12 = 0 0 + -9x = -3 + -12 -9x = -3 + -12 Combine like terms: -3 + -12 = -15 -9x = -15 Divide each side by '-9'. x = 1.666666667 Simplifying x = 1.666666667
| 5(3-x)=50 | | (z^2+z+0.5)= | | 3(y+9)=-6(4y-6)+9y | | 18+x=12+7x | | y-11=2(x-2) | | 5+-5=5+7 | | -7(w-4)=-5w+26 | | -2w+33=-9(w-6) | | (3+7i)(5+i)= | | -2.6(-2.6)+1.2y=7.8 | | 3z^2-9z/z-3 | | -2.6x=7.8 | | 235+.75d=125+1.63d | | -8x+4(x+2)=4 | | 1/(x^2-64)-3/(x-8)=1/(x+8) | | -2u+4(u-6)=-28 | | 7m-10=-4+5m | | 3x-5x-2= | | 2s-14=-26+5s | | 4r-25=-34+7r | | 9x-26=-5+2x | | 12x^3+16x^2=-5x | | 12*2900+174000= | | -3x-5x-27=29 | | x^2-4x+17= | | (Y-4/y-5)=(y-3/y+1)+1 | | 1/5X^2-2=5 | | -18=7v+9-10v | | 2x+34=45 | | 4(a+7b)+3a= | | 1/2(c+6)+7 | | -2y/9=8 |